Relationship between personal psychological capitals, stress level, and performance in marathon runners - Emily L.L. Sin, MSc; Chi-ngan Chow, MSc; Roy T.H. Cheung, PhD (World Scientific Publishing, 2015)
Background: Marathon runners experience different levels of stress from their performance, which may vary across different people. Objectives: This study sought to examine if stress levels could be predicted by running performance and personal psychological capitals, including optimism and self-efficacy levels in marathon finishers. It also determined the contribution of each component in a stress prediction model. Methods: An online questionnaire and comprised validated scales were used to measure runners' performance, perceived stress levels, and personal psychological capitals. Results: A positive correlation between runner performance and perceived stress level (rs = 0.256, p = 0.019) was found, while the personal psychological capitals were negatively correlated to stress levels (rs = −0.580, p < 0.001) and (rs = −0.618, p < 0.001) respectively. Perceived stress levels were best predicted by personal psychological capitals (β = −0.322-−0.393, p = 0.001), but not running performance. Conclusion: Our findings suggested that psychological factors affect stress levels the most, and marathon runners with a lower performance were more prone to stress than those who perform better.